2019
DOI: 10.1029/2018jd029596
|View full text |Cite
|
Sign up to set email alerts
|

Cloud‐Resolving Model Intercomparison of an MC3E Squall Line Case: Part II. Stratiform Precipitation Properties

Abstract: In this second part of a cloud microphysics scheme intercomparison study, we focus on biases and variabilities of stratiform precipitation properties for a midlatitude squall line event simulated with a cloud‐resolving model implemented with eight cloud microphysics schemes. Most of the microphysics schemes underestimate total stratiform precipitation, mainly due to underestimation of stratiform precipitation area. All schemes underestimate the frequency of moderate stratiform rain rates (2–6 mm/hr), which may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 89 publications
2
54
0
Order By: Relevance
“…Furthermore, Figure illustrates that both SR1 and SR2 IWPs are representative of 20–70% of their corresponding CC values in both the LS and PS cases, and up to 95% for the TS case, while their PRs are only 8–25% of their CC values. These values further confirm not only that the SR PRs may depend on IWPs but also that the microphysics properties of ice particles such as hydrometer types and size distribution may play an important role (Han et al, ). The variation in IWP values may also be represented by the differences in the thermodynamic properties shown in Table .…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Furthermore, Figure illustrates that both SR1 and SR2 IWPs are representative of 20–70% of their corresponding CC values in both the LS and PS cases, and up to 95% for the TS case, while their PRs are only 8–25% of their CC values. These values further confirm not only that the SR PRs may depend on IWPs but also that the microphysics properties of ice particles such as hydrometer types and size distribution may play an important role (Han et al, ). The variation in IWP values may also be represented by the differences in the thermodynamic properties shown in Table .…”
Section: Resultssupporting
confidence: 65%
“…Considering the possible mismatches between the CSA classification and radar‐derived precipitation due to surface wind, the grid boxes that were classified as SR but had PRs greater than 10 mm/hr have been excluded from the analysis for SR. The 10‐mm/hr threshold is often used to discriminate convective precipitation (Han et al, ; Leary & Houze, ; Penide et al, ; Wang et al, ), and previous studies have found that less than 3% of rain rates classified as stratiform are above the 10‐mm/hr threshold (Wang et al, ). The total precipitation amount of pixels having rain rates greater than 10 mm/hr account for less than 8% of the total stratiform precipitation amount in our analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The threshold of 15 mm hr −1 seems high because we use the instantaneous rain rate in every 6‐min frequency, not the hourly scale rain rate. This surface rain rate‐based separation follows Han et al (). As discussed in Han et al (), the radar reflectivity‐based methods (e.g., Steiner et al, ) may not be suited for potentially biased simulated radar reflectivity.…”
Section: Resultsmentioning
confidence: 99%
“…This surface rain rate‐based separation follows Han et al (). As discussed in Han et al (), the radar reflectivity‐based methods (e.g., Steiner et al, ) may not be suited for potentially biased simulated radar reflectivity. We have also tested with a different threshold such as 10 mm hr −1 , and the conclusion remains the same.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum snow mass content in all simulations occurs around the 6‐km layer, followed by a decrease toward the melting level. This behavior agrees with the simulations shown in Han et al (). It seems that despite a high variability, the observations do not show such a decrease in IWC in the 1‐km depth layer above the melting level.…”
Section: Resultsmentioning
confidence: 99%